Shear Characterization of Adhesive Layers by Advanced Optical Techniques - Leitão, A. C. C. (2016)
With adhesive bonding, design can be oriented towards lighter structures because of the direct weight savings over fastened or welded joints and also due to the flexibility to joint different materials. Cohesive Zone Models (CZM) are a powerful design tool, although the CZM laws of the adhesive bond in tension and shear are required as input in the models. This work experimentally evaluates the shear fracture toughness (GIIC) and CZM laws of bonded joints for three adhesives with distinct ductility. GIIC was characterized by conventional and the J-integral techniques. Additionally, by the J-integral technique, the precise shape of the cohesive law was defined. For the J-integral, a digital image correlation method is used to estimate the adhesive layer shear displacement at the crack tip (δs) during the test, coupled to a Matlab® sub-routine for extraction of this parameter automatically. As output of this work, fracture data is provided in shear for each adhesive, showing the marked differences between the three adhesives evaluated. This information enables the subsequent strength prediction of bonded joints under this mode of loading.